Association of coronary artery calcification with liver fibrosis in Japanese patients with non‐alcoholic fatty liver disease. (15th March 2016) - Ishiba, Hiroshi; Sumida, Yoshio; Kataoka, Seita; Kuroda, Masaaki; Akabame, Satoshi; Tomiyasu, Kiichiro; Tanaka, Muhei; Arai, Masahiro; Taketani, Hiroyoshi; Seko, Yuya; Okajima, Akira; Hara, Tasuku; et al.
Abstract : Aims: Cardiovascular events are the leading cause of death among patients with non‐alcoholic fatty liver disease (NAFLD), but their relationship remains unclear. This study examined the association between coronary atherosclerosis and liver fibrosis, represented by the coronary artery calcification (CAC) score and non‐invasive fibrosis markers, respectively. Methods: Among 698 patients with chest pain or electrocardiographic abnormalities who underwent coronary computed tomography (CT) between April 2006 and March 2010, those with known liver disorders or history of emergency coronary angioplasty were excluded, leaving 366 patients for this study. Diagnosis of NAFLD was based on abdominal CT and history of alcohol consumption. Subjects with CAC of 100 AU or more were categorized into the high‐risk group for cardiovascular events. Patient records were examined for clinical parameters including CAC score and non‐invasive fibrosis marker FIB‐4 index. Results: Ninety‐four patients (25.7%) had NAFLD. In this group, univariate analysis identified old age, high diastolic blood pressure, high liver to spleen ratio and high FIB‐4 index as risk factors for cardiovascular events and multivariate analysis identified age of 66 years or older and FIB‐4 index of 2.09 or more as the significant risk factors. For the observation period until August 2014, the cumulative proportion of PCI performance was significantly higher in patients with FIB‐4 of 2.09 or more than those with FIB‐4 of less than 2.09. Conclusion: The progression of arteriosclerosis and that of liver fibrosis may be associated in NAFLD patients. The FIB‐4 index can be easily determined and thus can be a useful marker for predicting cardiovascular events in NAFLD patients.